2022
DOI: 10.3390/ani12233418
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Glutamine on Rumen Digestive Enzymes and the Barrier Function of the Ruminal Epithelium in Hu Lambs Fed a High-Concentrate Finishing Diet

Abstract: The present experiment aimed to research the effects of glutamine (Gln) on the digestive and barrier function of the ruminal epithelium in Hu lambs fed a high-concentrate finishing diet containing some soybean meal and cottonseed meal. Thirty healthy 3-month-old male Hu lambs were randomly divided into three treatments. Lambs were fed a high-concentrate diet and supplemented with 0, 0.5, and 1% Gln on diet for 60 days. The experimental results show that the Gln treatment group had lower pepsin and cellulase en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…At present, the National Research Council (NRC) has not established dietary requirements for preruminants or ruminants (e.g., calves, beef cattle, dairy cows, lambs, and ewes) for Glu or Gln [ 75 , 121 ]. However, there is evidence that preruminants, as well as adult sheep, goats, dairy cows, and cattle, require dietary Glu ( Table 5 ) and Gln ( Table 6 ) supplementation for maximal growth and production performance, as well as for optimal (particularly intestinal) health and function, as detailed in the following sections [ 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 ]. This represents a paradigm shift in ruminant nutrition.…”
Section: Glu and Gln Nutrition In Ruminantsmentioning
confidence: 99%
See 3 more Smart Citations
“…At present, the National Research Council (NRC) has not established dietary requirements for preruminants or ruminants (e.g., calves, beef cattle, dairy cows, lambs, and ewes) for Glu or Gln [ 75 , 121 ]. However, there is evidence that preruminants, as well as adult sheep, goats, dairy cows, and cattle, require dietary Glu ( Table 5 ) and Gln ( Table 6 ) supplementation for maximal growth and production performance, as well as for optimal (particularly intestinal) health and function, as detailed in the following sections [ 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 ]. This represents a paradigm shift in ruminant nutrition.…”
Section: Glu and Gln Nutrition In Ruminantsmentioning
confidence: 99%
“…Based on the finding that dietary supplementation with Gln improved gastrointestinal integrity and function in young pigs [ 85 ], studies were conducted with lambs to determine the role of Gln in their ruminal functions. Specifically, Wu et al [ 141 ] reported that supplementing 0.5% or 1% Gln to a concentrate diet for 60 days enhanced the expression of claudin-1 and interleukin-10 (an anti-inflammatory cytokine) in ruminal epithelial cells by about 105% and 50%, respectively, in healthy 3-month-old male Hu lambs with an initial mean BW of 26.75 kg, compared with the control group. Furthermore, supplementation with 0.5% or 1% Gln increased pH, the ratio of acetate/propionate, and lipase activity in the ruminal fluid by about 4%, 25%, and 30% respectively, as well as the concentrations of interleukin-10 in serum by about 40% [ 141 ].…”
Section: Glu and Gln Nutrition In Ruminantsmentioning
confidence: 99%
See 2 more Smart Citations